Correlation of two radioimmunoassay systems for measuring plasma pregnancy‐associated glycoproteins concentrations during early pregnancy and postpartum periods in water buffalo. (12th September 2018) - Barbato, Olimpia; Menchetti, Laura; Sousa, Noelita M.; Brecchia, Gabriele; Malfatti, Alessandro; Canali, Claudio; Beckers, Jean‐Francois; Barile, Vittoria L.
Contents: This is the first time that PAG determination using two different antisera raised against PAG molecules purified from both caprine (RIA‐706) and bubaline placentas (RIA‐860) is reported in water buffalo. Ninety‐eight buffalo cows, belonging to a buffalo herd subjected to a synchronization and artificial insemination (AI) programme, were enrolled in this study. Blood samples were taken on days 0 (AI), 23, 25, 28, 30 and 45. Pregnancy was confirmed by ultrasonography on days 28 and 45. The blood of 20 buffaloes that had calved was tested every five days from the day of calving until day 50 postcalving. Differences in PAG concentrations were observed between pregnant and nonpregnant buffaloes starting from day 23 post AI using both RIA‐706 and RIA‐860 ( p  < 0.001). However, estimated mean concentrations of PAG measured by RIA‐706 were higher than RIA‐860 ( p  < 0.001) and Bland–Altman analysis showed biases ranged from 0.0 ng/ml at day 23 to 0.79 ng/ml at day 28 post AI. Moreover, RIA‐706 showed greater sensitivity and accuracy both at 23 and 25 days of pregnancy. RIA‐706 and RIA‐860 decreased below 1 ng/ml from 40 and 30 days postpartum, respectively, suggesting that PAG are better recognized by the antisera raised against the caprine PAG in the postpartum period also. This is essential when using PAG as an appropriate marker of early pregnancy after postpartum for detecting new pregnancies. The results of this study show that the ability of RIA systems to recognize early PAG could be improved using antisera raised against PAG molecules isolated from caprine placenta.